Pengaruh Kurs dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia : Akuntansi - Budi Santoso, Cahyo; Istiningrum, Rr.Farida (Fakultas Ekonomi, 2024)
ABSTRACT This study aims to look at the effect of exchange rates and world oil prices on the Composite Stock Price Index (JCI). The object of this study is the Composite Stock Price Index (JCI). The subject of this research is the Indonesia Stock Exchange. This research design is causality associative research and is a time series research. The data used is secondary data. The data analysis method used is multiple regression with a level of significance of 0.05. The variables in this study are the Composite Stock Price Index (CSPI), Exchange Rate, and World Oil Price. Based on the results of data analysis, the exchange rate has a negative and significant effect on JCI as evidenced by the exchange rate regression coefficient of 0.0816 with a significance value of 0.042. World Oil Price has no effect on JCI as evidenced by the regression coefficient value of World Oil Price of 0.278 at a significance of 0.073. The coefficient of determination is 25.4%. This indicates that 25.4% of the variation in the JCI dependent variable can be explained by the independent variables of Exchange Rate, and World Oil Price while the remaining 74.6% is explained by other factors not mentioned in this study. Keywords: JCI, Inflation, Exchange Rate, and World Oil Price